Electronic structure and atomic structure peculiarities of isomorphic modified zinc diphosphates - Smolyak, S.S.; Karbivskyy, V.L.; Kasiyanenko, V.H. (Functional Materials, 2014)
Effects of partial substitution of Zn by Mn on the electronic and atomic structure of diphosphates Zn₂₋xMnxP₂O₇⋅5H₂O (x = 0.0, 0.7) have been studied out by X-ray photoelectron spectroscopy, IR spectroscopy, NMR and thermogravimetric analysis. Analysis of the infrared absorption spectra was carried out for functional groups of Zn₂P₂O₇⋅5H₂O and Zn₁.₃Mn₀.₇P₂O₇5H₂O compounds. Through correlation between the symmetric and asymmetric stretching vibrations of P-O-P bridge and P-O-P angle an increase of P-O-P bridge angle was established for Zn₁.₃Mn₀.₇P₂O₇5H₂O. Substitution of zinc by manganese has little impact on the overall balance of chemical bond in the compound, which is manifested in minor changes of the core electrons binding energies.